Coved‐type ST‐elevation during ablation of ischemic ventricular tachycardia. Issue 5 (23rd March 2015) - Hori, Yuichi; Nakahara, Shiro; Tsukada, Naofumi; Nakagawa, Ayako; Hayashi, Akiko; Komatsu, Takaaki; Kobayashi, Sayuki; Sakai, Yoshihiko; Taguchi, Isao
Abstract: A coved‐type electrocardiogram (ECG) change in Brugada syndrome is suggested to be the result of abnormally delayed depolarization over the right ventricular outflow tract; however, ischemia of the conus branch of the right coronary artery presents the same ECG change. A 63‐year‐old man with a history of myocardial infarction demonstrated a transient coved‐type ECG change during catheter ablation of ventricular tachycardia. The ECG change appeared during left ventricular mapping without any chest symptoms, and recovered spontaneously. A pilsicainide test was negative and a coved‐type ECG did not appear during the perioperative or follow‐up period.